ROLE OF HYDROXY-ALUMINOSILICATE IONS (PROTO-IMOGOLITE SOL) IN THE FORMATION OF HUMIC SUBSTANCES - Liu C.; Huang P.M. (My University, 2002)
Little is known of the role of solution species of soil aluminosilicates in the formation of humic substances. Catalysis by hydroxy-aluminosilicate (HAS) ions, one of the major forms of soluble aluminum and silicon and the precursor of noncrystalline aluminosilicates in acidic natural environments, in catechol humification was investigated in this study by using UV-visible, FTIR, and solid state 13C CP-MAS NMR spectroscopies, X-ray diffractometry, atomic force microscopy, and elemental analysis. Hydroxy-aluminosilicate ions substantially promoted the oxidative polymerization and ring cleavage of catechol, resulting in the formation of black precipitates of humic macromolecules. This abiotic catalysis by HAS ions merits close attention in understanding the formation and related geochemistry of humic substances especially in acidic environments in temperate and subtropical regions.